Biotherapy - history, principles and practice : a practical guide to the diagnosis and treatment of disease using living organisms - Sherman, Ronald A.; Gileva, Olga S.; Kim, Christopher M.H; Mumcuoglu, Kosta Y.; Grassberger, Martin (Springer Netherlands, 2013)
Biotherapy as defined by the International Biotherapy Society is the use of living organisms in the treatment and diagnosis of human diseases. Although modern day Western medicine has often little understanding for living creatures in daily medical practice, there is a long-standing tradition in many of the biotherapy modalities. This volume is an evocative exploration of the history, scientific basis and practical use of living organisms in medicine. The authors provide researchers and practitioners interested in this field, with cutting-edge material on the latest key advances in the following fields of biotherapy: Maggot Therapy: The use of blowfly larvae for chronic wound treatment Hirudotherapy: The application of medicinal leeches for extraction of blood from congested or inflamed tissues, in a wide range of pathologies Bee Venom Therapy: The use of honey bee venom for the treatment of inflammatory diseases Apitherapy: The use of bee products for numerous chronic ailments. Ichthyotherapy: The use of small fresh-water fish for dermatological conditions such as psoriasis Helminth Therapy: The use of nematode worms as agents for stimulation of host immunological responses appropriate for the alleviation of certain inflammatory diseases Phage Therapy: The therapeutic use of bacteriophages to treat bacterial infections Animal Assisted Therapy: The application of dogs and horses for people with physical, psychological, cognitive, social, and behavioral problems Canine Olfactory Detection: The training of dogs to recognize medical conditions such as cancer and diabetic crises In addition, the authors provide with their chapters an extensive bibliography that represents a state-of-the-art survey of the literature. Comprehensive and current, this fresh volume of reviews is an essential resource for professionals who need to stay ahead of the game in the exciting field of biotherapy.